2018
DOI: 10.1177/1403494817743894
|View full text |Cite
|
Sign up to set email alerts
|

Economic poverty among children and adolescents in the Nordic countries

Abstract: This study showed that economic poverty among Nordic families with dependent children has increased during the latest decade, but it also showed that poverty rates are not necessarily connected to families' ability to make their money last. Therefore additional studies are needed to explore existing policies and political commitments in the Nordic countries to compensate families with dependent children living in poverty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…In contradiction to the previous findings (Kawamoto et al 2018; Le Vigouroux and Scola 2018; Mikolajczak et al 2018b) being unemployed or having a low income were significant predictors of burning out as a parent. These effects may be specific to Finland, as it has been shown that economic poverty in Finnish families with children has been increasing during the past decade (Povlsen et al 2018) and that poor families have significantly worse quality of life than those with better income (Karvonen and Salmi 2016). However, similar to the previous studies (Kawamoto et al 2018;Mikolajczak et al 2018) and in line with our expectations (Hypothesis 1), all family background variables together explained relatively little variance of parental burnout (8%).…”
Section: Discussionmentioning
confidence: 99%
“…In contradiction to the previous findings (Kawamoto et al 2018; Le Vigouroux and Scola 2018; Mikolajczak et al 2018b) being unemployed or having a low income were significant predictors of burning out as a parent. These effects may be specific to Finland, as it has been shown that economic poverty in Finnish families with children has been increasing during the past decade (Povlsen et al 2018) and that poor families have significantly worse quality of life than those with better income (Karvonen and Salmi 2016). However, similar to the previous studies (Kawamoto et al 2018;Mikolajczak et al 2018) and in line with our expectations (Hypothesis 1), all family background variables together explained relatively little variance of parental burnout (8%).…”
Section: Discussionmentioning
confidence: 99%
“…During the first 3 months after the implementation of the latest reform, the number of children under the age of 18 living in poverty increased by almost 11,000 to an all‐time high of 64,500 children (Caspersen & Damm, 2021; Ejrnæs et al, 2020; Juul, 2018; Povlsen et al, 2018; Schytz, 2018). Child poverty has previously been a relatively rare phenomenon in Denmark because generous social benefits and benefits that specifically target children have, to a large degree, prevented child poverty (Ejrnæs et al, 2020; Povlsen et al, 2018). This means that practices with vulnerable families in poverty have not been given much attention in the frontline.…”
Section: The Danish Social Policy Reforms: Their Logic and Core Elementsmentioning
confidence: 99%
“…This is something that they worry about and link to security in their everyday life, in line with the concept of human security. As we mentioned in the introduction, there has been increasing social inequality in Norway in the last few decades (Povlsen et al 2018), something that might explain their uncertainties regarding their economic future.…”
Section: Discussionmentioning
confidence: 98%
“…The universal welfare regime in Norway and the relatively low impact of the financial crisis in 2008 (Belmonte-Martín and Tufte 2017) might explain why the experience of risk and prosperity is different among our participants in northern Norway compared to those from other countries. However, there has been an identified increase in social inequality in Norway in the last decades (Povlsen et al 2018).…”
Section: Introductionmentioning
confidence: 99%